Theaflavin Attenuates TBHP-Induced Endothelial Cells Oxidative Stress by Activating PI3K/AKT/Nrf2 and Accelerates Wound Healing in Rats - Chen, Dalei; Wu, Zhijian; Wu, Lu-Ning; Jiang, Jingtao; Hu, Gui-Nv (Frontiers in Bioengineering and Biotechnology, 2022)
The treatment of wounds remains a clinical challenge because of poor angiogenesis under the wound bed, and increasingly, the patients' need for functional and aesthetically pleasing scars. Previous reports have shown that Theaflavin can induce angiogenesis and terminate the progression of ischemic cardiovascular disease, but limited therapy is available for the management of cutaneous wounds. In this study, our in vitro work discovered that human umbilical vein endothelial cells (HUVECs) exposed to Theaflavin can alleviate apoptosis and cell dysfunction induced by tert-butyl hydroperoxide (TBHP). The cellular activity of HUVECs were assessed by cell tube formation, migration and adhesion. Mechanistically, Theaflavin protected HUVECs from TBHP-stimulated cell apoptosis through the activation of the phosphatidylinositol-3-kinase (PI3K)/ protein kinase B (AKT)/ nuclear factor (erythroid-derived 2)-like 2 (Nrf2) axis, so Nrf2 silencing can partly eliminate the cytoprotective effect of Theaflavin treatment. In in vivo experiments, administering Theaflavin orally can enhance vascularization in regenerated tissues and accelerate wound healing. In summary, our data served as a novel evidence for the wound healing treatment with Theaflavin, and certified the potential mechanism of Theaflavin, which can be used as a potential agent for cutaneous wound therapy.